Chidamide as maintenance after chemotherapy or hematopoietic stem cell transplantation in 27 children with T-cell lymphoblastic leukemia: A real-world prospective study - Li, Xin-Yu; Han, Xia-Wei; Huang, Ke; Zhang, Ya-Ting; Xu, Hong-Gui; Zhou, Dun-Hua; Xu, Lu-Hong; Fang, Jian-Pei (Frontiers in Medicine, 2023)
Background The long-term overall survival of children with T-cell acute lymphoblastic leukemia (T-ALL) is limited to approximately 80–85% because of a high incidence of relapse after achieving remission with intensive chemotherapy and hematopoietic stem cell transplantation (HSCT). Novel treatment strategies inducing long-term remission are needed to improve the outcome. Histone deacetylase inhibitors (HDACis) have been reported to be effective in a series of T-ALL cases. Preclinical studies suggested that T-ALL cells are sensitive to Chidamide, which is a selective HDACi. Methods This preliminary clinical study evaluated the efficacy and safety of Chidamide in combination with chemotherapy or post-HSCT for children with T-ALL at a dose of 0.5 mg/kg weight of patient twice per week for at least 6 months. Results In total, 27 children with a mean age of 7.88 years were included. The high-risk proportion was 66.7%. After a median follow-up period of 37.8 months (9.5- 67.9 months), the overall survival and event-free survival in the patients treated with Chidamide were 94.1 % and 95.2 %, respectively. All patients except two maintained persistent remission with < 0.01% blast cells in minimal residual disease. Conclusions The combination therapy with Chidamide in a case series of T-ALL shows the promising clinical efficacy and good safety in children.